NOD2 Deficiency Promotes Intestinal CD4+ T Lymphocyte Imbalance, Metainflammation, and Aggravates Type 2 Diabetes in Murine Model - Carlos, Daniela; Pérez, Malena M.; Leite, Jefferson A.; Rocha, Fernanda A.; Martins, Larissa M. S.; Pereira, Camila A.; Fraga-Silva, Thais F. C.; Pucci, Taís A.; Ramos, Simone G.; Câmara, Niels O. S.; Bonato, Vânia L. D.; Tostes, Rita C.; et al. (Frontiers in Immunology, 2020)
Type 2 diabetes (T2D) is a metabolic disease characterized by increased inflammation and NOD-like receptors (NLRs) activation. New evidence supports an interplay between the gut microbiome and diabetes, but studies addressing T cell compartmentalization of NLR deficient mice and its implication on gut dysbiosis and obesity-induced T2D are poorly understood. In this context, we aimed to address whether NOD2 receptor drives intestinal helper T (Th) CD4+ lymphocyte immunity, shapes the gut microbiota and regulates obesity-induced type 2 diabetes (T2D) pathogenesis. Mice lacking NOD2 receptor fed a high-fat diet (HFD) display severe obesity, exhibit greater adiposity and more hepatic steatosis compared to HFD-fed wild-type (WT) mice. In addition, they develop increased hyperglycemia, worsening of glucose intolerance and insulin resistance. Notably, the deficiency of NOD2 causes a deviation from M2 macrophage and regulatory T cells (Treg) to M1 macrophage and mast cells into visceral adipose tissue (VAT) compared to WT mice fed HFD. Interestingly, an imbalance was also observed in Th17/Th1 cell population and cytokine profile in the mesenteric lymph nodes (MLNs) and ileum of NOD2-deficient mice fed HFD. 16S rRNA sequencing indicates lower richness, alpha diversity and a depletion of Allobaculum, Lactobacillus and enrichment with Bacteroides genera in these mice compared to HFD-fed WT mice. These alterations were associated with disrupted tight-junctions expression, endotoxemia and bacterial translocation into the VAT. Overall, NOD2 receptor activation is required for a protective Th17 over Th1 response in the gut, which appears to decrease gram-negative bacteria outgrowth and LPS translocation into VAT, attenuating metainflammation and confering protection against obesity-induced T2D.